2012
DOI: 10.4081/rt.2012.e39
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Plasma Cell Leukemia: A Single-Institution Experience in the era of Novel Agents

Abstract: Plasma cell leukemia (PCL) is a rare hematologic malignancy with aggressive clinical and biologic features. Data regarding its prognosis with the use of the novel agents, i.e., the immunomodulatory drugs thalidomide and lenalidomide, and the proteasome inhibitor bortezomib, are limited. We retrospectively reviewed clinical outcomes, response to therapy, and survival of 17 patients seen at the Penn State Hershey Cancer Institute since the availability of novel agents (2006–2011). Twelve patients had primary PCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is noteworthy that the OS was not reached in patients eligible for or treated with HSCT. However, the effectiveness of novel agents and HSCT are considered insufficient to overcome the adverse characteristics of PCL [11,23,24]. Drake et al [25] reported that auto-HSCT could improve the outcome of pPCL patients, but the OS was inferior to that achieved in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the OS was not reached in patients eligible for or treated with HSCT. However, the effectiveness of novel agents and HSCT are considered insufficient to overcome the adverse characteristics of PCL [11,23,24]. Drake et al [25] reported that auto-HSCT could improve the outcome of pPCL patients, but the OS was inferior to that achieved in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Osteolytic lesions have a lower prevalence than in MM. This can be explained by the fact that pPCL cells leave the bone marrow and enter the peripheral circulation before forming bone tumors, presumably because of a loss of homing signals in the bone marrow [ 1 , 4 ]. Our patient had thoracic pain and tumour which imitated an extensive chest bone neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of patients will have markedly elevated serum lactate dehydrogenase (LDH) levels and B 2 macroglobulin [1,14].…”
Section: Diagnosismentioning
confidence: 99%
“…Case Reports in Hematology abnormalities [5,8,15]. Majority of the PCL cases had translocation involving the immunoglobulin heavy-chain locus (IgH) on 14q32 such as t (11,14), t (4; 14), and t (14; 16). TP53 inactivation, MYC translocations, and mutations in K-RAS and N-RAS were among those documented with PTEN deletion which cause Akt activation being more in sPCL.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation